2019
DOI: 10.22487/j26223090.2019.v1.i2.11884
|View full text |Cite
|
Sign up to set email alerts
|

Adopsi XBRL Terhadap Perilaku Perdagangan Investor Di Bursa Efek Indonesia

Abstract: This study aims to investigate the impact of XBRL adoption to trade behavior of investors in the Indonesia Stock Exchange which is reflected by frequency of stock trade. The sample of this study is 34 banks taken randomly from 81 banks listed in the Indonesia Stock Exchange in 2014 and 2016. The data analysis methods used in this study are one way ANOVA for difference test and multiple regression analysis to test the impact of ROA, size and dividend ratio to XBRL adoption. This study found that the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The second hypothesis (H2) on this study stated that company size on value relevance is acceptable with positive influence. The results of the study were in line with Razak et al (2019) research, testing the size of XBRL pre and post-adoption showed significant levels of 0.000. This indicated that the size affects the response of XBRL, meaning that small companies respond from XBRL.…”
Section: Size Has a Positive Effect On Value Relevancesupporting
confidence: 84%
See 3 more Smart Citations
“…The second hypothesis (H2) on this study stated that company size on value relevance is acceptable with positive influence. The results of the study were in line with Razak et al (2019) research, testing the size of XBRL pre and post-adoption showed significant levels of 0.000. This indicated that the size affects the response of XBRL, meaning that small companies respond from XBRL.…”
Section: Size Has a Positive Effect On Value Relevancesupporting
confidence: 84%
“…There is no relationship between the adoption of XBRL and the value relevance of earnings. The result indicated that XBRL does not make financial statements more informative and showed that there is no difference in the pre and post-adoption of XBRL as well as the new XBRL implementation on the Indonesian stock exchange in 2015, so XBRL trading information has not shown a positive response from investors (Razak et al, 2019).…”
Section: The Electronic Financial Disclosure That Adopts Xbrl Has a P...mentioning
confidence: 99%
See 2 more Smart Citations